2017
DOI: 10.1002/lno.10723
|View full text |Cite
|
Sign up to set email alerts
|

Using small‐scale measurements to estimate hypolimnetic oxygen depletion in a deep lake

Abstract: Low oxygen concentrations in lakes and reservoirs are an ongoing environmental concern, particularly in light of increasing anthropogenic activity and climate change. Oxygen depletion processes in lakes are still not completely understood and a variety of models have been proposed based on limited field observations. Here, we present field measurements of oxygen depletion processes in a deep lake, Lake Geneva (Switzerland). The aim of this study was to quantify three basic processes controlling hypolimnetic ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 60 publications
2
37
0
Order By: Relevance
“…Diffusive oxygen uptake (DOU) rates at the sediment water interface were in the range or slightly higher than those available in the literature for acid lakes (Kühl et al 1998;Koschorreck et al 2003;Lagauzère et al 2011) and neutral lakes (Sweerts et al 1991;Maerki et al 2009;Matzinger et al 2010;Schwefel et al 2017). The instantaneous increase in O 2 concentration in the HI-OX transition probably induced an increase in the oxidation rates of organic matter and reduced compounds like Fe 2?…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Diffusive oxygen uptake (DOU) rates at the sediment water interface were in the range or slightly higher than those available in the literature for acid lakes (Kühl et al 1998;Koschorreck et al 2003;Lagauzère et al 2011) and neutral lakes (Sweerts et al 1991;Maerki et al 2009;Matzinger et al 2010;Schwefel et al 2017). The instantaneous increase in O 2 concentration in the HI-OX transition probably induced an increase in the oxidation rates of organic matter and reduced compounds like Fe 2?…”
Section: Discussionmentioning
confidence: 89%
“…The effect of hypolimnetic hypoxic and anoxic conditions on degradation and preservation rates of organic matter and the regeneration and release of nutrients from lake sediments has received considerable attention (Maerki et al 2009;Matzinger et al 2010;Schwefel et al 2017). However, the number of studies dealing specifically with the effects of reversible redox oscillations on the biogeochemistry of lake sediments is scarce (Borch et al 2010;Frindte et al 2013;Torres et al 2014;Karimian et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…n.d., not determined. Some data were taken from the respective literature: 1 Frenzel et al (1990), 2 Span et al (1990), 3 Schwalb et al (1998), 4 Müller et al (2007), 5 Zimmermann (2008), 6 Putyrskaya et al (2009), 7 Sobek et al (2009), 8 Wirth et al (2011), 9 Bierlein et al 2017, 10 Steinsberger et al (2017), 11 Schwefel et al (2018). to SOU, while in Lake Geneva and Lake Thun, due to high loads from the catchment geology, SO 4 2− fluxes contributed about one third to SOU.…”
Section: Sediment Oxygen Uptake Dependence On Organic Mattermentioning
confidence: 99%
“…Studies of Lakes Michigan (Thomsen et al 2004), Erie (Edwards et al 2005;Smith and Matisoff 2008), and Superior (Li et al 2012) have further demonstrated the importance of SOU and/or WCM as O 2 sinks in these lakes. A study of the highly productive and deep Lake Geneva by Schwefel et al (2018) showed that, as with the Great Lakes, O 2 consumption primarily occurred in the water column rather than near or in the sediment.…”
mentioning
confidence: 99%
See 1 more Smart Citation